Social Panorama of Latin America and the Caribbean 2024 - United Nations Economic Commission for Latin America; the Caribbean (United Nations, 2025)
This edition of the Social Panorama of Latin America and the Caribbean, 2024 addresses the challenges of non-contributory social protection to advance towards inclusive social development in the region. Addressing the development crisis, the gaps in inclusive social development and the reconfiguring risk structure requires progress towards universal, comprehensive, sustainable and resilient social protection systems. Non-contributory social protection policies are essential in achieving the objectives and functions of social protection systems: income protection, access to social services and labour inclusion. One in three households in the lowest income quintile lacks access to social protection and programme amounts are often insufficient to overcome poverty. The region faces persistent gender inequality and a care crisis that will be exacerbated by accelerated ageing. Progress in poverty eradication requires comprehensive policies, as well as progress in establishing a standard of social investment in non-contributory social protection.